2017
DOI: 10.4172/2157-7420.1000277
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perception and Choice Factors Related to International Hospitals: A Study in Ho Chi Minh City, Vietnam

Abstract: In the background of stagnant home markets, health care firms from mature economies are looking for opportunities in developing markets such as Vietnam. Various studies on marketing of health care from developed economies show convenience, specialties, reputation, and word of mouth as major choice factors for hospitals. The limited number of consumer behaviour articles from developing economies has contradictory findings for private and public hospitals with no mention of international hospitals. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, researchers have stated that price is not a primary determinant when choosing private hospitals. 5 Instead, inpatients in emerging markets rely on convenience, turnaround time, specialties, reputation, and word-of -mouth in their decision-making process of private healthcare services. A previous study has also shown that the clinic's delivery methods, such as customer-oriented care and amenities, might be more important than perceptions of physician's technical skills and treatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers have stated that price is not a primary determinant when choosing private hospitals. 5 Instead, inpatients in emerging markets rely on convenience, turnaround time, specialties, reputation, and word-of -mouth in their decision-making process of private healthcare services. A previous study has also shown that the clinic's delivery methods, such as customer-oriented care and amenities, might be more important than perceptions of physician's technical skills and treatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, a different ranking of factors was reported by patients. For example, a study in Vietnam (2017) declared that factors such as comfort, specialties, reputation, and word of mouth were the factors effecting hospital choice [14].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted internationally to understand patient perceptions on healthcare quality, patient satisfaction with health services, how healthcare quality can be assessed and the choice factors of healthcare services. [5,11,12,13] Research identified many factors that can affect patient satisfaction: reliability, responsiveness, assurance, tangible factors such as physical infrastructure, communication, empathy, orderly management of healthcare services, cost and availability/access are some of the main facets.…”
Section: Discussionmentioning
confidence: 99%
“…International studies reveal when patients decide to obtain private healthcare services, price is not a primary concern, [13] but patients do expect a higher level of service from private sector healthcare, and this phenomenon may hold true in Sri Lanka as well. However, in the more affluent western world [15] and [16] suggest that healthcare consumers have become much more sensitive to costs, despite health insurance coverage.…”
Section: Doctor's Feementioning
confidence: 99%